Heart rate and VO2 responses to treadmill running with body weight support using the GlideTrak™ - Jordan Perry; Wayne Johnson; Gilbert W. Fellingham; Pat R. Vehrs (Elsevier, 2017)
Background/Objective: The heart rate (HR) and metabolic (VO2) responses to treadmill running using the GlideTrak™ body weight support system have not been reported. The purpose of this study was to compare the submaximal and maximal HR and VO2 responses to normal-weight treadmill running (TMR) to treadmill running with body weight support provided by the GlideTrak™ (GTR). Methods: Twenty participants (11 males; 9 females) 18 to 26 years of age voluntarily participated in this study. Each participant completed two exercise tests in each mode of running: a maximal graded exercise test to compare maximal HR and VO2 values and a submaximal exercise test to compare the HR-VO2 relationship. Results: Maximal HR and VO2 values were significantly (p < 0.001) lower during GTR (183.4 ± 9.1 bpm, 38.1 ± 7.2 mL kg−1 min−1) compared to TMR (194.3 ± 8.6 bpm, 49.5 ± 8.9 kg−1 min−1). There was a significant difference in the HR-VO2 relationship between GTR and TMR. Compared to TMR, exercising at a HR of 140 bpm resulted in a VO2 that was 4.0 mL kg−1 min−1 lower during GTR. At the VO2 associated with a HR of 140 bpm during TMR, the HR during GTR was 16 bpm higher. During GTR at intensities of exercise up to an RER of 1.0, only 8 participants achieved vigorous intensities of aerobic exercise defined as 64-90% of VO2max. Conclusion: Exercising with the GlideTrak™ body weight support system may not provide the same cardiorespiratory training stimulus as normal-weight treadmill running.